ECONOMIC ORGANIZATIONAL BASIS OF HIGHER EDUCATION MANAGEMENT - Isamiddinovna, Nizamova Shoira (Antis Publisher, 2024)
In this article, in the development of higher education The existing funding mechanism and its shortcomings National higher education financial support for development national doctrine of support procedural to form - dynamic approach, its financing system three main conceptualizations of change support support on the existing theory views , in particular, in general theoretical the foundations of the economy development theory , financial in the social sphere of management research was conducted on the general theories and the theory of financial management in managing the financial support of the development of higher education and methodical levers , is available financing paradigms pedagogical approaches are reflected